MWCNT for ambient urea synthesis - Yahya, N. (Elsevier B.V., 2018)
Entangled multiwall carbon nanotubes have been synthesized by means of the floating catalyst technique for ambient urea synthesis. MWCNT were prepared by the spray pyrolysis of ferrocene ethanol mixture at a temperature of 1200 Â°C and atmospheric pressure in the presence of N2 as carrier gas. The X-ray diffraction graph reveals the establishment of hexagonal structure of MWCNT. FE-SEM results show the formation of carbon nanotubes (CNT) with diameter ranging between 26 and 65 nm. The VSM hysteresis loops depicts that the saturation magnetization values for MWCNT were 1.03 emu/g because of high purity of CNT (99.5). The nanotubes were used as catalyst for ambient urea synthesis at ambient conditions in the presence of unidirectional constant magnetic field. The use of lower flow rate (for better adsorption) and reaction time (to stop reverse reaction) with high magnetic field gives an increased yield of urea because of enhanced triplet harvesting (Zeeman splitting). The peak yield of urea, 10118 ppm was accomplished by applying 1.25 T of magnetic field and using 0.25 L/min flow rate for a reaction time of 1 min. Â© 2018